Analisis Kinerja Bidan Dalam Penatalaksanaan Manajemen Aktif Kala III Dan Antisipasi Perdarahan Postpartum Primer Di Kabupaten Tapanuli Utara Tahun 2015 - Marni Siregar; Sulastry Pakpahan; Ganda Simbolon (Jurnal Reproductive Health, 2017)
Third stage active management and anticipation of primary postpartum haemorrhage is one of the basic competencies of midwives. During the period of 2013 - August 2015 there are 25 cases of maternal deaths in North Tapanuli, with the biggest cause factor is bleeding. This study aims to analyze the performance of midwives in the implementation of third stage active management and anticipation of postpartum bleeding in North Tapanuli Regency in 2015. This study is a quantitative study with cross sectional approach. Sampling was done by purposive sampling method that is midwife who helped normal delivery and anticipate primary postpartum haemorrhage in September-October 2015 (32 people). Data were collected through observations and a valid and reliable questionnaires. Analysis of data used univariate, bivariate analysis with Pearson product moment correlation and multivariate analysis with multiple linear regression. The results showed that midwives' performance was mostly in poor category (62,50%). Logistic regression test showed that education variables had the greatest and significant effect on midwife performance, followed by knowledge, motivation and experience. Age, employee status, workload, and coworkers have no effect on midwife performance with p-value> 0,05. Form of regression equation obtained performance = 6,476 +1,038 X1 + 0,500 X2 + 0,369 X3 +0,324 X4 + e. R Square value of 0.995 so that obtained coefficient of determination (KD) is 99.5% which means that independent variables have a contribution influence of 99.5% to Y and 0.5% other influenced by other factors not included in this study. This study concludes that education, motivation, experience and knowledge have a significant influence in the management of active management at the third stage and anticipation of postpartum hemorrhage